Sri Lankan Patterns of Female Cancers: Incidence and Mortality Over 1995-2010 - Vithana, Palatiyana V. S. C; Dheerasinghe, Dompeyalage S. A.F; Handagiripathira, Hadagiripathira M. I; Alahapperuma, Shreeni; Nilaweera, Irosha; Perera, Suraj (Asian Pacific Journal of Cancer Care, 2021)
Background: Neoplasms are the second leading cause of deaths in Sri Lanka. Present study analysed the trends in incidence and mortality of all cancers, breast cancer, cervical, ovarian and uterine cancers among Sri Lankan females over 1995-2010. Methods: Cancer incidence was obtained from national hospital-based cancer registries. Cancer mortality was abstracted from World Health Organization database and Department of Census and Statistics Sri Lanka. Number of new cases and deaths were obtained by five-year age group for all cancers by sex and breast, cervical, ovarian and uterine cancers for females. Particular cancer specific incidence and mortality rates were directly age-standardised to the Segi-Doll world standard population. Age-standardised incidence and mortality for young adults (20-34 years), adults (35-64 years) and older adults (over 64 years) by the type of the female cancer over 1995-2010 were calculated. Results: Age-standardised rates for incidence for all cancers among females rose from 63.3 to 87.5 per 100 000 population during 1995-2010 and its morality increased from 44.5 to 53.5 per 100 000 population. In spite of having similar trends in both sexes, cancer incidence among females remained higher while mortality persisted lower than males. Breast cancer was the commonest cancer among females with its incidence and mortality increasing through-out. Cervical cancer incidence increased during 1995-2000, declined slightly in 2005 and remained stable over 2006-2010.Cervical cancer mortality remained stable over 1995-1999, declined in 1999-2003, increased slightly throughout 2003-2006 and remained stable during 2007-2010. Ovarian cancer incidence remained stable over 1995-2010. Its mortality remained stable over 1995-2000, declined slightly during 2000-2003 and increased in 2003-2010. Uterine cancer incidence and mortality increased steadily throughout 1995-2010. For all these cancers, incidence and mortalityin 0-34 years remained low. Conclusions: Increasing trend of cancer incidence and mortality among females over 1995-2010, directs the need of revisiting female cancer control programmes.